2006
DOI: 10.1590/s0101-81752006000200025
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on distribution of four Sciaenidae species (Actinopterygii, Perciformes) in a tropical bay at Southeastern Brazil

Abstract: We sampled fish and measured environmental variables in the Sepetiba Bay, a tropical embayment at Southeastern Brazil. The aim was to assess environmental influences on distribution of four abundant species of Sciaenidae Micropogonias furnieri (Desmarest, 1823), Ctenosciaena gracilicirrhus (Metzelaar, 1919), Cynoscion leiarchus (Cuvier, 1830) and Menticirrhus americanus (Linnaeus, 1758) to test the habitat partition hypothesis. Samples were taken between June 1993 and July 1996, at three bay zones (outer, cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
1
16
0
4
Order By: Relevance
“…These juveniles probably use the area to feed during the summer and then spread to deeper water at other times of the year. The same results were found by Araújo (2006) at Sepetiba bay (Rio de Janeiro state, Brazil). This explains the lesser abundance of this species in the sample collected in winter in Palmas bay.…”
Section: Discussionsupporting
confidence: 83%
“…These juveniles probably use the area to feed during the summer and then spread to deeper water at other times of the year. The same results were found by Araújo (2006) at Sepetiba bay (Rio de Janeiro state, Brazil). This explains the lesser abundance of this species in the sample collected in winter in Palmas bay.…”
Section: Discussionsupporting
confidence: 83%
“…For MUTO et al (2000) the spatial organization exhibited by the ichthyofauna along a depth gradient in the São Sebastião system (southeastern Brazil) were closely related to the distribution of the water masses which are characterized by different combinations of salinities and temperatures. Even so, it is believed that the type of substrate will have influences on both prey and demersal fish distribution, as most species live in a close association with the bottom (ARAÚJO et al 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, BALDÓ and DRAKE (2002) suggested that the mysids (hyperbenthic) replace copepods (zooplanktonic) progressively in the diet of juvenile fish (2006) found that the grazing fish, which kept a roughly balanced diet between microphytobenthos and detritus, changed their exclusively herbivorous diet during summer to prey on nematofauna during winter on a mudflat. This fluidity among guilds exists because ecological interactions among species are intensified at certain periods, with the less competitive species or species more susceptible to predation being excluded or replaced by species with greater adaptability to environmental pressures (ARAÚJO et al, 2006). Although ontogenetic changes were not specifically examined in the present study, some authors have asserted that certain species may segregate into different guilds during growth (LEGUERRIERA et al, 2007;ABDURAHIMAN et al, 2010).…”
Section: Discussionmentioning
confidence: 87%